2007
DOI: 10.1074/mcp.m700123-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

A Proteomics Study of Brassinosteroid Response in Arabidopsis

Abstract: The plant steroid hormones brassinosteroids (BRs) play an important role in a wide range of developmental and physiological processes. How BR signaling regulates diverse processes remains unclear. To understand the molecular details of BR responses, we performed a proteomics study of BR-regulated proteins in Arabidopsis using two-dimensional DIGE coupled with LC-MS/MS. We identified 42 BR-regulated proteins, which are predicted to play potential roles in BR regulation of specific cellular processes, such as si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
147
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 184 publications
(154 citation statements)
references
References 100 publications
7
147
0
Order By: Relevance
“…Several lines of evidence indicate that using IP linked to mass spectrometry analysis is a powerful tool to identify true interactors of the BRL3 receptor complex. First, we purified the BRL3 receptor complex in Arabidopsis and identified a number of interactors of BRI1, which have been previously characterized as BR signaling components (Li et al, 2002;Deng et al, 2007). In addition, our analysis revealed a number of potential interactors that coimmunoprecipitated with the BRL3 receptor protein.…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence indicate that using IP linked to mass spectrometry analysis is a powerful tool to identify true interactors of the BRL3 receptor complex. First, we purified the BRL3 receptor complex in Arabidopsis and identified a number of interactors of BRI1, which have been previously characterized as BR signaling components (Li et al, 2002;Deng et al, 2007). In addition, our analysis revealed a number of potential interactors that coimmunoprecipitated with the BRL3 receptor protein.…”
Section: Discussionmentioning
confidence: 99%
“…"sup" identifies m␤cd responsiveness based on release of these proteins to the supernatant after pelleting m␤cd-treated plasma membranes. Letters indicate proteins previously published as being GPI-anchored (gpi) (35,36,50,51) …”
Section: Core List Of Proteins Identified As M␤cd-responsive In At Lementioning
confidence: 99%
“…Glutathione and its metabolic enzymes interact with plant growth regulators, which are regarded as vital in the scheme of plant establishment both under normal and stressful conditions. GST expression in plants is induced by phytohormones such as SA, ethylene, cytokinin, auxin, ABA (Marrs 1996), methyl jasmonate (Moons 2003), and brassinosteroids (Deng et al 2007). Chen et al (2012) demonstrated that GST overexpressed in Arabidopsis thaliana plants had a signaling role and it regulated plant development by maintaining GSH pools.…”
Section: Droughtmentioning
confidence: 99%